Clarifying the Relationship of Dissociative Experiences to Suicide Ideation and Attempts: A Multimethod Examination in Two Samples. Issue 5 (September 2021) - Pachkowski, Mikayla C.; Rogers, Megan L.; Saffer, Boaz Y.; Caulfield, Nicole M.; Klonsky, E. David
Abstract: Fears of pain, injury, and death may represent key barriers to acting on suicidal thoughts. Dissociation, which involves a disconnection from one's body, may reduce fears and sensations of pain associated with harming the body, in turn facilitating suicide attempts. This study examined whether dissociation differentiated individuals with a history of suicide attempts from those with a history of suicide ideation, and investigated whether other relevant constructs explain this relationship. Sample 1 included 754 undergraduates ( M age  = 21, 79% female) who completed a battery of self-report measures. Sample 2 included 247 undergraduates ( M age  = 19, 74% female) who completed a self-report measure of dissociation, a clinical interview regarding suicide history, and four counterbalanced behavioral pain tolerance tasks. In both samples, dissociation was elevated in lifetime attempters compared to ideators ( d  = 0.28; d  = 0.46; p s = 0.01) and slightly elevated in lifetime ideators compared to nonsuicidal individuals ( d  = 0.19, p  = .02; d  = 0.24, p  = .47), though this effect was non-significant in the latter sample. In Sample 1, dissociation no longer differentiated attempters from ideators after controlling for clinical covariates. In Sample 2, dissociation was unrelated to behavioral pain tolerance tasks, and these tasks did not account for the association between dissociation and attempts. Overall, dissociation differentiated individuals with a history of suicide attempts from those with ideation alone in both samples. Pain tolerance did not explain this association; instead, it is possible that the relationship of dissociation to suicide attempts is due to "third variables" associated with both phenomena, such as symptoms of borderline personality disorder or posttraumatic stress disorder.